Multiple gastric tumors in patients with combined autoimmune and helicobacter pylori-associated gastritis: a case report and literature review - Lin, Wulian; Wu, Cuiling; Xu, Guilin; Yi, Gaocheng; Zhang, Guanpo; Li, Haitao; Zheng, Jin; Li, Dazhou; Wang, Wen (Frontiers in Immunology, 2025)
This paper presents four cases of autoimmune gastritis coexisting with Helicobacter pylori- associated gastritis, all of which developed gastric tumors, with some cases exhibiting multiple histological origins. Through a narrative literature review, we explore the potential mechanisms and clinical implications of tumor development in this context. This report emphasizes the significance of recognizing synergistic mucosal injury in chronic gastritis management and highlights the need for future studies into combined pathogenesis.